Design and Development of A Single Page and Web-based Responsive E-learning System for Higher Education Institutions - Khan, Muhammad Lookman Hossain; Setiawan, Agus; Kustiawan, Iwan (INVOTEC, 2019)
Students now use not only computers or laptops, but also small devices such as mobile phones. The students at higher education institutions spent a lot of time on the internet to find the course materials. Sometimes the teacher sends the materials, but the students who are willing to take a specific course of a semester cannot get a brief concept of the course on before starting the semester. There is now a lot of online education systems on the Internet, but few are a single page and responsive. The purpose of this research is to develop a single page, responsive and web-based e-learning system. The method used in this research is the Rapid Application Development approach which has six stages of the development process, namely Planning, Analysis, Design, Implementation, Testing, and Maintenance. This research was conducted in the Faculty of Technology and Vocational Education, Universitas Pendidikan Indonesia. The students and teachers from the Department of Mechanical Engineering Education participated in this research. The results of this research indicate that with fully functional live chat, the OpenCourseWare system has a high usability test score, highly responsive and awesome features. The OpenCourseWare system is responsive and ajax-based mobile-friendly system that can be used by higher education institutions as an e-learning system based on the results obtained.